Ultrasound-Guided Posterolateral Approach for Midline Calcified Thoracic Disc Herniation - Tan, Lee A. (The Korean Neurosurgical Society, 2014)
OBJECTIVE: Symptomatic thoracic disc herniation often requires prompt surgical treatment to prevent neurological deterioration and permanent deficits. Anterior approaches offer direct visualization and access to the herniated disc and anterior dura but require access surgeons and are often associated with considerable postoperative pain and pulmonary complications. A disadvantage with using posterior approaches in the setting of central calcified thoracic disc herniation however, has been the limited visualization of anterior dura and difficulty to accurately assess the extent of decompression. METHODS: We report our experience with intraoperative ultrasound (US) guidance during a modified posterior transpedicular approach for removal of a central calcified thoracic disc herniation with a review of pertinent literature. RESULTS: The herniated thoracic disc was successfully removed with posterior approach with the aid of intraoperative US. The patient had significant neurological improvement at three months follow-up. CONCLUSION: Intraoperative ultrasound is a simple yet valuable tool for real-time imaging during transpedicular thoracic discectomy. Visualization provided by intraoperative US increases the safety profile of posterior approaches and may make thoracotomy unnecessary in a selected group of patients, especially when a patient has existing pulmonary disease or is otherwise not medically fit for the transthoracic approach.